Effectiveness of Village-Based Organization (VBO) in improving the livelihood of the rural community in Bangladesh (Bangladesh Journal of Public Administration, 2020)
The study's overarching objective was to evaluate the pros and cons of the newly adopted Village-Based Organization that was funded by the United Nations' Food and Agriculture Organization (FAO). Empirical data was collected following personal interviews and focus group discussions.  The study revealed that VBO contributed to diversifying enterprises by promoting high-value crops, small-scale livestock, and other value-added activities. The respondents expressed their complimentary views about their uplifted living standards. The women’s active participation and consequent empowerment increased by restoring their rights on resources and decision making. Farmers Field School motivated the community to introduce new technologies and practices for maintaining their livelihoods better. Despite some limitations, the VBO helped reduce local disputes and criminal activities like dowry, the high-interest rate of credit, child marriage, and drug abuse. The study advocates replicating this concept in the whole country as a part of the corona pandemic stimulus package. It can curb Monga (seasonal famine), tackle incremental anthropogenic-climatic stressors, reduces the consumption of natural resources, achieves Sustainable Development Goals, and finally, uphold the aspiration of a "whole society approach" and "no one is left behind." Policy interventions are warranted to rectify the identified challenges and integrate the basic principles of sustainability, termed a holistic approach.